2020
DOI: 10.3390/en13174357
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Interior and Exterior Bearing Structures of the Deep-Soft-Rock Roadway: From Theory to Field Test in the Pingdingshan Mining Area

Abstract: Pingdingshan mining area is one of the typical deep mining areas in China, and most of the mines in this area are troubled by the difficulties of the deep-soft-rock roadway support. Based on the concept of synergistic interactions of the interior and exterior bearing structure of the surrounding rock and, considering the specific geological conditions of the research site, we establish the mechanical model of the interior and exterior bearing structure of the roadway. Based on numerical simulation, we reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…After roadway excavation, the plastic damage degree and range of the surrounding rock both increase, and the soft surrounding rock is prone to overall roof subsidence, rib bulge, and floor structural rheology. Statistics found that 90% of underground deep soft-rock roadways have been repaired at least once [3][4][5][6]. Considering the stability of the roadway surrounding rock, it is of great significance to analyze the time-dependent damage of deep soft-rock roadways and propose effective support measures.…”
Section: Introductionmentioning
confidence: 99%
“…After roadway excavation, the plastic damage degree and range of the surrounding rock both increase, and the soft surrounding rock is prone to overall roof subsidence, rib bulge, and floor structural rheology. Statistics found that 90% of underground deep soft-rock roadways have been repaired at least once [3][4][5][6]. Considering the stability of the roadway surrounding rock, it is of great significance to analyze the time-dependent damage of deep soft-rock roadways and propose effective support measures.…”
Section: Introductionmentioning
confidence: 99%
“…Rocks surrounding the coal seams are generally very weak [3,7]. Increasing mining depth due to high in-situ stress, high overburden, and tectonic stress causes the surrounding rock to undergo large nonlinear deformation [8], making it soft [9], e.g., the Pingdingshan mining area [10], Yili No. 1 Coal Mine [11], Xiaokang Coal Mine [12], Xin'an coal mine in Gansu Province [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The stress concentration phenomenon after the excavation of the cavern in the deep and weak rock mass may cause the stress level of the rock mass to exceed the strength of the surrounding rock, forming a plastic stress area. Plastic shear slip or plastic flow tends to increase the risk of construction and threaten the quality and safety of the project [4][5][6][7][8]. Therefore, it is extremely necessary to calculate the stability limit displacement of surrounding rock for deep-buried soft rock tunnel construction [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%